MANAJEMEN LABA, TINDAKAN PAJAK AGRESIF, DAN PERAN TATA KELOLA PERUSAHAAN: STUDI PADA PERUSAHAAN DI JAKARTA ISLAMIC INDEX - Bayu Seno Pitoyo; Nurmala Ahmar; Suyanto Suyanto (STES Islamic Village, 2019)
This study examines the efffect of earnings Management on Aggressive Tax action with The Audit Committee, Institutional Ownership and Independent Commissioners are positioned as moderating variables. The sample data of this research are 96 companies in the time of 2012-2017 obtained from JII (Jakarta Islamic Index). The descriptive statistics were analyzed using Wrap PLS 0.6 program. Hypothesis testing is eximined by Structural Equation Model - Partial Least Square (SEM-PLS) using Wrap PLS 0.6 program.The finding of this study proves that earning management has an effect on aggressive tax action. Institutional ownership can moderate the effect of earnings management on aggressive tax action. Independent board commissioners can moderate the effect of earnings management on aggressive tax action. The audit committee cannot moderate the effect of earnings management on aggressive tax Action.